1995
DOI: 10.1016/0092-8674(95)90015-2
|View full text |Cite
|
Sign up to set email alerts
|

The secretory phospholipase A2 gene is a candidate for the Mom1 locus, a major modifier of ApcMin-induced intestinal neoplasia

Abstract: Mutations in the APC gene are responsible for various familial and sporadic colorectal cancers. Min mice carry a dominant mutation in the homolog of the Apc gene and develop multiple adenomas throughout their small and large intestine. Quantitative trait loci studies have identified a locus, Mom1, which maps to the distal region of chromosome 4, that dramatically modifies Min-induced tumor number. We report here the identification of a candidate gene for Mom1. The gene for secretory type II phospholipase A2 (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
372
0
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 539 publications
(388 citation statements)
references
References 42 publications
14
372
0
2
Order By: Relevance
“…Patients whose gastric cancers expressed PLA2G2A, the gene encoding the group IIa secreted phospholipase A2, at high levels, had a highly significant survival advantage (p Ͻ 0.002). The murine ortholog of PLA2G2A, has been shown genetically to limit the severity of intestinal neoplasia in the Apc min1/ϩ mouse, a mouse model of familial adenomatous polyposis, suggesting that PLA2G2A may play a similar role in suppressing progression of human gastric cancer (MacPhee et al, 1995;Cormier et al, 1997). A more extensive analysis and discussion of the association between PLA2G2A and gastric cancer progression is reported separately (Leung et al, 2002).…”
Section: Expression Patterns Significantly Correlated With Patient Sumentioning
confidence: 98%
“…Patients whose gastric cancers expressed PLA2G2A, the gene encoding the group IIa secreted phospholipase A2, at high levels, had a highly significant survival advantage (p Ͻ 0.002). The murine ortholog of PLA2G2A, has been shown genetically to limit the severity of intestinal neoplasia in the Apc min1/ϩ mouse, a mouse model of familial adenomatous polyposis, suggesting that PLA2G2A may play a similar role in suppressing progression of human gastric cancer (MacPhee et al, 1995;Cormier et al, 1997). A more extensive analysis and discussion of the association between PLA2G2A and gastric cancer progression is reported separately (Leung et al, 2002).…”
Section: Expression Patterns Significantly Correlated With Patient Sumentioning
confidence: 98%
“…Combination of Min and Mom1 leads to an increase of lifespan and reduced tumor number. The Mom1 gene encodes a secretory phospholipaseA2 (MacPhee et al, 1995). For more information about this and other modi®ers we refer the interested readers to an article by Dove and colleagues in this issue.…”
Section: Genetic Basis For Colorectal Cancermentioning
confidence: 99%
“…In addition, the multiple intestinal neoplasia (Min) mouse, a model for human familial adenomatous polyposis, demonstrates the modification of disease by genetic background. Min mice differ greatly in the number of intestinal tumors, depending on the mouse strain carrying this mutation (27,28). Recently, studies have shown that the gene encoding the group II secretory nonpancreatic PLA 2 (sPLA 2 ) enzyme is naturally disrupted in a number of inbred mouse strains and has been identified as a candidate gene for the modifier of the Min 1 (Mom1) locus (27,28).…”
mentioning
confidence: 99%